2020
DOI: 10.1097/md.0000000000019430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of photobiomodulation on orthodontic movement of molar verticalization with mini-implant

Abstract: Introduction: Loss of a dental element can generate several repercussions in the stomatognathic system. According to the latest survey by the Ministry of Health, in 2010, Brazilian adults had, on average, 7 missing teeth. This loss may lead to movement of the adjacent teeth and the antagonist, which would make prosthetic rehabilitation harder to do. Anchoring systems, such as mini-implants, have been increasingly used as a treatment option because they act with heavy but controlled forces and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…In current studies, although the effects of CGF on tissue regeneration are available, the information about its effect on tissue damage mechanisms is not clear. In addition, studies conducted today have reported that CGF suppresses TNF-α and NF-kB/p65 expressions [30]. Similarly, Xu et al…”
Section: Discussionmentioning
confidence: 94%
“…In current studies, although the effects of CGF on tissue regeneration are available, the information about its effect on tissue damage mechanisms is not clear. In addition, studies conducted today have reported that CGF suppresses TNF-α and NF-kB/p65 expressions [30]. Similarly, Xu et al…”
Section: Discussionmentioning
confidence: 94%
“…3.3 Improve occlusal stability: after the first molar loss, if no intervention is applied, the adjacent teeth will tilt to the missing side and the elongation of the jaw teeth will occur [6], Affect the occlusal relationship, and then affect the masticatory function of the missing tooth side. The nearmiddle movement of the second molar can fill the loss after the first molar extraction, improve occlusal stability, and reduce the impact of masticatory and occlusal function.…”
Section: The Advantage Of Orthodontic Retention Of the Third Molars A...mentioning
confidence: 99%
“…En concordancia, evidencia baja y con cierto sesgo indica que la irradiación de LLLT de onda de 780nm, la fluencia de 5 J/cm2 y/o la potencia de salida de 20 mW podría acelerar el MOT en 2 y 3 meses según un metaanálisis (Long et al, 2015) Agregando a lo anterior, la PBM también tiene efectos, antiinflamatorios y analgésicos, en tal sentido, esta terapia ayudaría a que el movimiento dentario se presente con menos dolor y menor producción de citocinas inflamatorias, lo que indicaría una modulación a la respuesta inflamatoria y por consecuente se acelera el MOD, por tla motivo, ha recibido gran atención en ortodoncia. (Malaquias et al, 2020) El modo de actuar del láser de diodo se basa en dos determinantes; el tipo de absorción (intermedia) y la longitud de onda responsable de la profundidad de penetración (relacionada inversamente). (Yavagal et al, 2021) Este aumento en la producción de ATP puede acelerar la remodelación ósea al estimular la actividad metabólica.…”
Section: • Terapia Fotodinamica (Tfd) Laserunclassified